Pelatihan dan Pendampingan Pemahaman Instruksi Bahasa Inggris dalam Pembuatan Buku Digital Untuk Guru ICBB Putri - surip Haryani (ABDIMAS Madani, 2022)
TRAINING AND ASSISTANCE IN UNDERSTANDING ENGLISH INSTRUCTIONS IN MAKING DIGITAL BOOK FOR TEACHERS WHO IMPLEMENTS ONLINE LEARNING ICBB PUTRI ABSTRACT During the Covid-19 pandemic, almost all schools carried out online or online learning, including the women's SU/SD and early childhood education at the Islamic Center Binbaz (ICBB). There are many limitations and shortcomings of online learning methods, including the abundance of digital files/documents that make the teacher's cell phone full of memory storage. One way to overcome this problem is to create a digital book that can be made online and taken from a website that provides free digital book formats, namely www.ebookcreator.com. The website is available in English so training and assistance in making digital books were provided. The training was conducted on Saturday, August 28, 2021 at 08.30 – 12.00 at the hall of RA Bunayya ICBB. The training participants were female teachers of SD/SU ICBB and PAUD&RA Bunayya with a total of 22 participants. Guidance on understanding the English guidelines on the website was given during the training and step-by-step guidance on making digital books. All participants directly practiced making digital books using their laptops. Each participant was guided to make the digital book from the stage of creating a new account, creating and choosing the type of digital book that suits the teaching needs to the final stage of how to distribute the digital book that has been completed in the form of a link to students and parents. It is hoped that this training and mentoring will provide great benefits for teachers in conducting online learnin